2018
DOI: 10.1007/s00277-018-3359-9
|View full text |Cite
|
Sign up to set email alerts
|

A higher percentage of cells with 13q deletion predicts worse outcome in Chinese patients with chronic lymphocytic leukemia carrying isolated 13q deletion

Abstract: Previous studies showed that, in chronic lymphocytic leukemia (CLL) patients with isolated 13q deletion (13q-), those carrying higher percentage of leukemic cells with 13q- had more aggressive diseases. However, the prognostic value of the percentage of leukemic cells with 13q- in Chinese CLL patients with isolated 13q- remained to be determined. Using interphase fluorescence in situ hybridization (FISH), we identified 82 patients (25.4%) with isolated 13q deletion from a cohort of 323 untreated CLL patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…We used peripheral blood/bone marrow samples to detect cytogenetic, molecular, and immunophenotypic aberrations. FISH was conducted to detect del(17p), del(11q), del(13q), and trisomy 12 according to the procedures described previously [20] . FISH probes included: LSI D13S319 for detection of del(13q14), LSI ATM for detection of del(11q22.3), CEP12 (centromere 12) for detection of trisomy 12 and LSI p53 for detection of del(17p13).…”
Section: Methodsmentioning
confidence: 99%
“…We used peripheral blood/bone marrow samples to detect cytogenetic, molecular, and immunophenotypic aberrations. FISH was conducted to detect del(17p), del(11q), del(13q), and trisomy 12 according to the procedures described previously [20] . FISH probes included: LSI D13S319 for detection of del(13q14), LSI ATM for detection of del(11q22.3), CEP12 (centromere 12) for detection of trisomy 12 and LSI p53 for detection of del(17p13).…”
Section: Methodsmentioning
confidence: 99%
“…Despite that, the clinical course of CLL cases with 13q-is diverse. Some patients exhibit a more aggressive clinical course and die rapidly, even after starting treatment at the time of diagnosis [35,57]. This is the reason why 13q14 deletions should be further classified as monoallelic or biallelic.…”
Section: Discussionmentioning
confidence: 99%
“…CLL patients with isolated 13q deletion have better prognosis than CLL patients with nonisolated del(13q). However, it is known that CLL patients with isolated del(13q) have heterogeneity in terms of prognosis (OS, TTFT) (6). It is suggested that the reason behind this heterogeneity, may be the size of the 13q deletion, deletion rate and additional gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the rate of mutation detected in the SF3B1 gene in cases with non-isolated 13q deletion was reported as 0% and the rate of mutation in the relevant gene in isolated del(13q) cases was reported as 4.8%. The researchers stated that the mutations of the genes were associated with high del(13q) ratio (> 80%) (6). Although the deletion rate of 13q was > 80% in the case with detected NOTCH1 gene mutation, no mutation was detected in the other 9 cases with > 80% deletion rate.…”
Section: Discussionmentioning
confidence: 99%